Effects of Ginseng Peptides on Laxative in Mice - Qiannan WANG; Wen YANG; Tingfang XUE; Jiaqi ZOU; Tao FENG; Lei YU; Yunfeng BI; Lina WANG (Shipin gongye ke-ji)
Objective: To study the moisturizing and laxative effects of ginseng peptides (GPs) on the constipation model of ICR mice, and provide theoretical basis for the further development and utilization of GPs and clinical adjuvant treatment of constipation. Methods: Sixty adult male ICR mice were randomly divided into 6 groups, they were normal group (NG), constipation group (CG), whey protein group (WPG), low-dose GPs group (LG), medium-dose GPs group (MG), high-dose GPs group (HG). Except NG, mouse constipation model was established using loperamide hydrochloride (LH). After 7 consecutive days of intervention with GPs, the small intestine peristalsis and defecation time, as well as pathological changes in the small intestine villus tissue of each group of mice were observed and compared. The improvement effect of GPs on mouse constipation was evaluated by detecting the content of brain gut peptide indicators in the serum of each group of mice, including substance P (SP) and vasoactive intestinal peptide (VIP). Results: Compared with the model group, the high, medium, and low dose groups of GPs significantly increased the small intestine ink advance rate in mice (P<0.01), which could alleviate the pathological damage of small intestine villi in constipated mice. Compared with the model group, the high-dose GPs group significantly shortened the first black stool excretion time (P<0.01), increased the number of fecal particles (P<0.05), and significantly increased fecal weight within 5 hours (P<0.01) in mice. The serum levels of substance P (SP) and vasoactive intestinal peptide (VIP) were significantly increased in the high and medium dose groups of GPs mice (P<0.01), while the low dose group of GPs increased the levels of brain intestinal peptide indicators SP and VIP in constipated mice (P<0.05). Conclusion: GPs has a significant laxative effect on a constipated mouse model, promoting small intestinal peristalsis, alleviating small intestinal villus damage, and promoting the expression of brain gut peptide markers SP and VIP in mice.